Antidiarrheal potential of Nigella sativa L. infusion in mice: a phytochemical and efficacy evaluation - Safitri, Nadiya; Mustika, Aulia Andi; Pristihadi, Diah Nugrahani; Sutardi, Lina Noviyanti; Purohita, Adwisto Saktika (Current Biomedicine, 2025)
Background Nigella sativa L., commonly known as black cumin, is a medicinal plant widely recognized for its therapeutic properties. However, limited pharmacological evidence supports its antidiarrheal potential when prepared as an infusion. Objective This study aimed to evaluate the phytochemical composition and antidiarrheal efficacy of Nigella sativa infusion in mice. Methods A total of 30 mice were divided into five groups: negative control (Tween 80 [1%]), positive control (Loperamide HCl), and treatment groups receiving Nigella sativa infusion at concentrations of 25%, 50%, and 100%. Antidiarrheal activity was assessed using the intestinal protection method, with parameters including defecation frequency, stool consistency, diarrheal onset time, and diarrheal duration. Results Phytochemical analysis revealed the presence of flavonoids, alkaloids, tannins, and saponins in Nigella sativa infusion. The infusion demonstrated significant antidiarrheal activity across all tested concentrations (25%–100%), with the 50% concentration showing the highest efficacy, comparable to Loperamide in reducing defecation frequency, improving stool consistency, delaying diarrheal onset, and shortening diarrheal duration. Conclusion Nigella sativa infusion at 50% concentration exhibits promising antidiarrheal potential and warrants further development as a herbal remedy.